2001
DOI: 10.1038/sj.onc.1204665
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 transcriptional activity requires ATM's kinase domain and multiple N-terminal serine residues of p53

Abstract: The ATM protein kinase regulates the cell's response to DNA damage by regulating cell cycle checkpoints and DNA repair. ATM phosphorylates several proteins involved in the DNA-damage response, including p53. We have examined the mechanism by which ATM regulates p53's transcriptional activity. Here, we demonstrate that reintroduction of ATM into AT cells restores the activation of p53 by the radio-mimetic agent bleomycin. Further, p53 activation is lost when a kinase inactive ATM is used, or if the N-terminal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 61 publications
(131 reference statements)
2
55
0
3
Order By: Relevance
“…HeLa Tip60mt cells had decreased basal kinase activity that was not activated by exposure to bleomycin. ATM's kinase activity is required for ATM to regulate cell survival after exposure to IR (17). The failure to fully activate ATM in HeLa Tip60mt cells implies that these cells should be more sensitive to IR.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa Tip60mt cells had decreased basal kinase activity that was not activated by exposure to bleomycin. ATM's kinase activity is required for ATM to regulate cell survival after exposure to IR (17). The failure to fully activate ATM in HeLa Tip60mt cells implies that these cells should be more sensitive to IR.…”
Section: Resultsmentioning
confidence: 99%
“…2a). The ability of ATM to phosphorylate and activate key target proteins is required for ATM to regulate the cell response to ionizing radiation (21). Because the FATC domain of ATM is adjacent to the kinase domain, the FATC domain may influence the ability of ATM to phosphorylate key target proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with current concepts proposing posttranslational modification of p53 at either the N-or Cterminus to affect stability regulation in general, with serine 15-phosphorylation being a prerequisite for the transcriptional activity of p53 in particular (Dumaz and Meek, 1999). Studies with p53 N-terminal mutations at serines 15, 20, 33 or 37 indicated multiple and functionally overlapping phosphorylation sites to control p53 activity in response to DNA damage (Shieh et al, 1997;Dumaz and Meek, 1999;Hirao et al, 2000;Turenne et al, 2001). Whether kinases such as ATR or DNA-PK, known to be involved in post-translational modification of p53, are engaged in transmitting the NO signal needs further investigations.…”
Section: Discussionmentioning
confidence: 99%